Reward and psychopathological correlates of eating disorders: The explanatory role of leptin. (August 2020) - Cassioli, Emanuele; Rossi, Eleonora; Squecco, Roberta; Baccari, Maria Caterina; Maggi, Mario; Vignozzi, Linda; Comeglio, Paolo; Gironi, Veronica; Lelli, Lorenzo; Rotella, Francesco; Monteleone, Alessio Maria; Ricca, Valdo; et al.
Highlights: High leptin levels are negatively associated with dietary restraint and physical exercise. High leptin levels are positively associated with binge eating and emotional eating. In multivariate analyses, leptin levels might explain the association between BMI and pathological behaviors. Leptin seems to have a role in the maintaining of reward-related pathological eating behaviors. Abstract: It has been hypothesized that leptin level alterations in Eating Disorders (EDs) represent a maintaining factor for pathological reward-related ED behaviors, given leptin role in the dopaminergic reward systems. The aim of the present study was to evaluate the role of leptin in EDs as a mediator for the relationship between Body Mass Index (BMI) and several pathological behaviors, such as dietary restraint, compensatory exercise, vomiting, binge eating and emotional eating. Sixty-two patients with EDs and 41 healthy controls (HC) had their blood drawn and completed psychometric tests for the evaluation of general psychopathology, ED psychopathology and emotional eating. Moderated linear regression models showed that, in the presence of high levels of ED psychopathology, leptin levels were negatively associated with dietary restraint and compensatory exercise, and positively with emotional eating and binge eating. Finally, leptin showed an indirect effect on the association between BMI and all these reward-related behaviors. These results suggest that a variation of BMI maintains these pathological ED behaviors through a variation in leptin levels. Considering the role of leptin in reward circuits, the results seem to confirm an aberrant food-related reward mechanism in ED patients.